ANALISIS KEMENARIKAN DESAIN WEBSITE, REPUTASI VENDOR, DAN PERSEPSI KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN BELANJA ONLINE DENGAN PERSEPSI NILAI PELANGGAN SEBAGAI VARIABEL INTERVENING - Fachmi, Mochammad Ilham; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to demonstrate the factors that influence online shopping decisions. By looking at previous studies, it was concluded there is the attractiveness of the website design, vendor reputation and perceived ease of transaction as factors affecting purchasing decisions online. To better understand these factors in influencing purchase decisions online, this study used the intervening variable customer's perception of value This study takes the basic concept of TAM. Then modified according to the variables that have a relationship with online purchasing decisions. The study found that the vendor 's reputation and perceived ease of transactions has a direct influence on purchase decisions online. While the attractiveness of the website design is only indirectly influenced by the perception of customer value . Furthermore , the reputation of the vendor does not have an indirect effect through the customer's perception of value . So that only the perceived ease of transactions that have direct and indirect influence on purchasing decisions online through an intervening variable perceived customer value.